Visual histories of Austria - Bischof, Günter, 1953- (University of New Orleans Press, 2021)
"Visual histories in 19th and 20th century Austria are documented here, from court photography and nature photography to political photography. A single photo studio will be analyzed documenting lives in Western Austria as well as a photo archive and its special collections regarding mountains. Imperial Austria is present in the pictures of court photographer Ludwig Angerer. Photos of wars figure heavily in this volume, from the brutal fighting in the Dolomites during WWI to National Socialism, concentration camps and the air war during WW II. Postwar life and the American presence in Austria will be documented from the end of the war to the postwar occupation--seen through the lenses of U.S. star photographer Yoichi Okamoto. Cartoons will be analyzed and the role of exhibits in modern public diplomacy"-- Provided by publisher
"This volume was conceived out of a panel in the 2019 German Studies Association meeting Portland, Oregon (Kofler/Siller, Markova, and Richter papers)."--Introduction
Keywords: Photography in historiography.; Museums and photography -- Austria.; Austria -- Historiography.; Photography -- Austria -- History -- 20th century.; Photographers -- Austria -- History -- 20th century.; Archives -- Austria.; Pictures as information resources -- Austria.; Photographie en historiographie.; Musées et photographie -- Autriche.; Photographie -- Autriche -- Histoire -- 20e siècle.; Photographes -- Autriche -- Histoire -- 20e siècle.; Archives -- Autriche.; Illustrations, images, etc. (Sources d'information) -- Autriche.; HISTORY -- Europe -- Austria & Hungary.; Archives; Historiography; Museums and photography; Photographers; Photography; Photography in historiography; Pictures as information resources; Austria; 1900-1999; History